2009
DOI: 10.1007/s00418-009-0659-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of P2X6 receptors in the enteric nervous system of the rat gastrointestinal tract

Abstract: Expression of P2X(4) and P2X(6) receptor subunits in the gastrointestinal tract of the rat was studied with double-labeling fluorescence immunohistochemistry. The results showed that P2X(6) receptors were expressed widely in the submucosal and myenteric plexuses. In the myenteric plexus, P2X(6) receptors were expressed mainly in large size neurons which resembled Dogiel type II neurons. These P2X(6) receptor-immunoreactive (ir) neurons also expressed calbindin 28K, calretinin and neuronal nuclei (NeuN), protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 40 publications
1
23
0
2
Order By: Relevance
“…For fluorescence immunocytochemistry, whole-mount preparations were used to perform a quantitative analysis as described previously (Van Nassauw et al 2002;Yu et al 2010). Briefly, positively stained neuron bodies in the submucosal and myenteric ganglia were counted per visual field (area: 0.62 mm 2 ).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…For fluorescence immunocytochemistry, whole-mount preparations were used to perform a quantitative analysis as described previously (Van Nassauw et al 2002;Yu et al 2010). Briefly, positively stained neuron bodies in the submucosal and myenteric ganglia were counted per visual field (area: 0.62 mm 2 ).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…In our previous work, double-labeling experiments demonstrated that about 10-25 % of neurons with P2X2 immunoreactivity in the myenteric plexus and 30-50 % in the submucosal plexus expressed Calbindin, a marker for intrinsic sensory neurons [11]. Co-expression of P2X2 with neuronal nitric oxide synthase, choline acetyltransferase, and Calretinin in neurons of the small intestine myenteric plexus was detected [30] [12]. While one can speculate on the overlap of P2X2-ir/Pirt-ir cells with the above cell types, more information is needed to identify the cell type for a better understanding of the role of Pirt protein in the gut.…”
Section: Discussionmentioning
confidence: 94%
“…In rats, P2X2-and P2X3-immunoreactive (ir) neurons were found in the myenteric and submucosal plexuses throughout the entire length of the digestive tract from the stomach to the colon [11]. P2X6 receptors were expressed widely in the submucosal and myenteric plexuses, and P2X4 receptors were not expressed in neurons but were expressed in macrophages of the gastrointestinal tract [12]. In mouse, P2X5 receptor immunoreactivity was widely distributed in myenteric and submucosal plexuses throughout the gastrointestinal tract [13].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to previous studies concerning expression of P2X receptor subunits P2X2, 3 and 5 in the gastrointestinal tract of various animals, Yu et al (2010) extended work on the P2 £ 4 and P2 £ 6 receptors in the rat gastrointestinal tract. The authors observed in the submucosal and myenteric plexus intrinsic sensory neurons to be positive only for P2 £ 6 receptor.…”
Section: Peripheral Nervous Systemmentioning
confidence: 96%
“…As such receptors form only heteromultimers with either P2 £ 2 or P2 £ 4 receptors (North 2002). Yu et al (2010) concluded that ATP, which acts on P2X receptors and plays a role of an excitatory neurotransmitter in the CNS, PNS (sympathetic neurons) and ENS (enteric ganglia) (Burnstock 2007;Dunn et al 2001), is probably involved in regulating physiological functions of submucosal/myenteric plexus neurons through a heteromeric P2 £ 6/2 receptor subunit makeup. Stubinger et al (2010) focused on the chemical coding of, and synaptic inputs to the intrinsic choroidal neurons in the chicken eye.…”
Section: Peripheral Nervous Systemmentioning
confidence: 98%